1987
DOI: 10.1149/1.2100713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fabrication Damage in GaAs Wafers

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Polishing damage has been investigated by X-ray techniques in both silicon and gallium arsenide. [13][14][15] Iida and Kohra showed a distinct difference in the omega rocking curve intensity between lapped, scratched, and etched Si surfaces using a triple crystal X-ray diffractometer. 13 Kuwamoto et al inspected the mechanical damage in gallium arsenide with X-ray diffraction omega rocking scans.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Polishing damage has been investigated by X-ray techniques in both silicon and gallium arsenide. [13][14][15] Iida and Kohra showed a distinct difference in the omega rocking curve intensity between lapped, scratched, and etched Si surfaces using a triple crystal X-ray diffractometer. 13 Kuwamoto et al inspected the mechanical damage in gallium arsenide with X-ray diffraction omega rocking scans.…”
mentioning
confidence: 99%
“…13 Kuwamoto et al inspected the mechanical damage in gallium arsenide with X-ray diffraction omega rocking scans. 14 A comparison of the peak width between lapped, cut, and etched GaAs surfaces showed that etching removes the damaged surface layers and, in turn, narrows the peak width and increases its intensity. Wang and Matyi used grazing incidence XRD and inclined Bragg plane XRD for the inspection of chemical mechanical polishing of GaAs.…”
mentioning
confidence: 99%
“…Diffraction peak broadening was exhibited by gallium arsenide (GaAs), indium phosphide (InP), and BT ceramics after mechanical processing treatment such as slicing, lapping, and/or polishing. 22,25,26) The lowered peak intensities and predominant peak broadening in polished ceramics are related to the impact of mechanical processing. On the other hand, with thermal annealing, the diffraction peaks which were shifted slightly to lower 2θ angles after polishing treatment were shifted to higher 2θ angles with increased peak intensities and sharpness.…”
Section: Resultsmentioning
confidence: 99%
“…The broadening of diffraction peaks with lowered peak intensities has been ascribed to the surface damage. 19) In unpoled polycrystalline tetragonal piezoelectric ceramics with randomly oriented domains, the ratio of the intensities of the two peaks (I (002) /I (200) ) is expected to be ³0.5, although the ratio is usually 0.58 in the unstressed state. 20) The value of the intensity ratio higher than 0.5 indicates that the c-domains are preferentially existed by polishing.…”
Section: Resultsmentioning
confidence: 99%